Targeted and tailored diagnostic strategies in women withperimenopausal bleeding: advantages of the sonohysterographic approach - Verrotti, C.; Benassi, G.; Caforio, E.; Nardelli, G. B. (Acta Biomedica Atenei Parmensis, 2008)
Background and aim of the work: Diagnosis and treatment of endometrial pathology nowadays ranges from clinical examination to transvaginal ultrasound (TVS), saline infusion sonohysterography (SIS), hysterosalpingography (HSG) and hysteroscopy (HYS). However, many gynaecologists prescribe blind endometrial biopsies, such as Vacuum ABRAsion (VABRA), as single strategy. The purpose of this work is to evaluate whether the procedure of VABRA should still be performed alone in perimenopausal women with abnormal uterine bleeding, compared to biopsies and samples obtained after a previous transvaginal sonohysterography. Methods: We retrospectively reviewed the records of 216 patients referred to our Ultrasonography and Day-Surgery Center between November 2005 and December 2006 with persistent premenopausal uterine bleeding, spotting or postmenopausal bleeding. One hundred and five out of 216 pts.(48.6%), defined as Group “A”, underwent a sole endometrial sampling by VABRA; 111 out of 216 pts. (51.4%), Group “B”, had a SIS first. Results: Vabra showed a poor sensitivity in the diagnosis of polyps (19%) and submucosal myoma, with a negative predictive value of 73.4%. Likelihood ratio for test negative was 0.81, with an overall diagnostic accuracy of 75%. Conclusions: This study confirms that blind endometrial biopsies should no longer be performed as the only diagnostic strategy in perimenopausal women with abnormal uterine bleeding. On the other hand, a sonohysteroscopy-guided approach allows an accurate detection of focal lesions; nevertheless, it should not be forgotten that SIS is an ultrasound based procedure, and may provide further information on endometrial thickness, myomas, ovaries and pelvis.